Twenty-Five Years of MALL Experimental Implementation Studies: What Do We Really Know About It - Athanasiou, Androulla; Burston, Jack (My University, 2020)
This chapter offers a comprehensive, up-to-date overview of Mobile-Assisted Language Learning (MALL) studies, from the first in 1994 through 2018, relating to the experimental implementation of mobile-based affordances and applications in the teaching and learning of languages, L1 as well as L2. It derives from the analysis of over 2000 MALL studies that have appeared in almost 500 distinct journals and presentations in conferences given by nearly 300 different professional organizations, the great majority of both sources being unrelated to language learning and teaching. It provides background information relating to these studies, documents their profoundly atheoretical nature, details their pedagogical features, and assesses their learning outcome effectiveness.
Keywords: Mobile-Assisted Language Learning